PEMBERIAN BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR (POC) TERHADAP PERTUMBUHAN DAN HASIL PADI RATUN - Nurul Istiqomah; Mahdiannoor Mahdiannoor; Fetty Asriati (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Ratoon paddy is one alternative that can be developed by farmers as the plant after the first rice harvest. Ratun rice is chicks of rice that grow back after the main rice was harvest. Utilization of ratoon paddy aims to increase the productivity of paddy for  a growing season. The giving of liquid organic fertilizer (LOF) can be improve the physical, chemical and biological of soil, help improve crop production, increase product quality of plants. LOF can provide the nutrient needs of the plants on land, because its liquid so if there is overcapacity of fertilizer on the ground then the plant  itselfwill be easy to regulate the absorption of fertilizer composition is needed. This  research aims at (i) to know how the giving of various concentrations of LOF to growth and yield of the ratoon paddy, (ii) to get the best concentrations of  LOF  to growth and yield of the ratoon paddy. This research was carried out in Wawai Village of Batang Alai Selatan District, Hulu Sungai Tengah Regency in March - June 2016, using Randomized Group Design (RGD), with 4 treatments and 6 repeat with 4 plants as the sample so that there are 96 plants were observed. The factors tested are  the concentration of the LOF there are p0 = without LOF, p1 = 3 mℓ / ℓ water, p2 = 6 mℓ / ℓ water, p3 = 9 mℓ / ℓ water. The results of this study show that treatment of the concentration LOF has very real influence for high plant at the age of 10, 20 and 30 Day After Spray Treatment (DAST), number of leaves at the age of  10, 20 and 30 DAST, number of chicks at the age of 10, 20 and 30 DAST, number of panicles, weight of grains, and number of grains. The best treatment is p3 with a concentration of 9 mℓ / ℓ water.